A fundamental viewpoint on the hydrogen spillover phenomenon of electrocatalytic hydrogen evolution - Jiayuan Li (Nature Portfolio, 2021)
Despite the significance of hydrogen spillover on metal-supported electrocatalysts for hydrogen evolution, fundamental understandings on such a process are insufficient. Here the authors show that small work function difference between metal and support facilitates hydrogen spillover and enhances activity.